Korean American Women's Experiences with Smoking and Factors Associated with Their Quit Intentions. (24th August 2013) - Kim, Sun S.; Kim, Seongho; Seward, Gregory; Fortuna, Lisa; McKee, Sherry A.
Abstract : This study explored Korean American women's experiences with smoking and tested the theory of planned behavior to identify factors associated with their intentions to quit smoking. It employed a mixed-methods research design, using qualitative and quantitative data. Participants were recruited via a combination of random ( N = 49) and convenience ( N = 45) sampling techniques. Women in this study initiated smoking at age of 23 on average, and nearly half smoked at indoor houses. They initiated smoking out of curiosity about the effect and belief that smoking would relieve their stress. Reasons for continued smoking were (a) to avoid nicotine withdrawal symptoms, (b) to cope with life stressors, including acculturative stress, and (c) to fulfill one's destiny as a lifetime smoker. Many attempted to quit due to health issues and pregnancy. Fear of disclosure and limited English proficiency were found to be major barriers to seeking help for quitting. Past-year quit attempt(s), attitudes toward quitting, and perceived family norm favoring quitting explained 25% of the variance in intentions to quit smoking (F [ 3, 90 ] = 11.58, P < 0.001 ). Findings suggest that gender- and culture-specific intervention strategies are needed to assist Korean American women in smoking cessation.